Pers Tionghoa Pasca Orde Baru di Yogyakarta - MAULANA, REZZA (Komunikator, 2013)
Since the end of Soeharto regime in 1998, dozens of newspapers with Chinese language and Indonesian newspapers which were published by Chinese people started to emerge. Having bases in some major cities, these newspapers aimed for all Chinese community. However, most of them did not exist in a long period. Interestingly, some of the Chinese press in some regions goes along in some certain pages in the local newspapers, such as in Yogyakarta. With this format, they can survive and become the media of expression for Indo-Chinese people. This paper essentially observes these phenomena in three Yogyakarta local newspapers, namely Bernas Jogja, Radar Jogja, and Harian Jogja (Harjo). Keywords: politic of recognition, identity, minority, contestation, media business